2019
DOI: 10.1073/pnas.1902820116
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing the metastable superhard material wurtzite boron nitride by three-dimensional networks of planar defects

Abstract: Wurtzite boron nitride (w-BN) is a metastable superhard material that is a high-pressure polymorph of BN. Clarifying how the metastable high-pressure material can be stabilized at atmospheric pressure is a challenging issue of fundamental scientific importance and promising technological value. Here, we fabricate millimeter-size w-BN bulk crystals via the hexagonal-to-wurtzite phase transformation at high pressure and high temperature. By combining transmission electron microscopy and ab initio molecular dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The Raman spectrum of Fig. 3 is consistent with the Raman spectrum of a millimeter-sized w-BN bulk crystal obtained by a high-pressure, high-temperature transformation recently reported [49]. The w-BN frequencies calculated by Ohba et al [43] using LDA ab initio methods are indicated on Fig.…”
Section: H-bnsupporting
confidence: 85%
“…The Raman spectrum of Fig. 3 is consistent with the Raman spectrum of a millimeter-sized w-BN bulk crystal obtained by a high-pressure, high-temperature transformation recently reported [49]. The w-BN frequencies calculated by Ohba et al [43] using LDA ab initio methods are indicated on Fig.…”
Section: H-bnsupporting
confidence: 85%
“…Chen et al [ 23 ] have discovered a stabilization mechanism for w -BN (produced utilizing the high pressure/high temperature approach) based on 3D networks of planar defects that are formed by dense network of intersecting stacking faults (ISF) and inversion domain boundaries (IDB). When the two orthogonal planar defects penetrate each other, an ISF–IDB junction is constructed to create a partial dislocation [ 23 , 56 ]. In GaN thin film, the empirical potential calculation model has shown that the ISF–IDB junction has low formation energy [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Boron nitride is not found naturally; it has to be produced from boron and nitrogen precursors. Different methods and experimental conditions have been used to synthesize BN from a variety of boron and nitrogen precursors [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Preparation of boron nitride (BN) was reported from high pressure/high temperature synthesis using diamond anvil cell/laser heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) A detailed observation of the fine structure of this wBN revealed an extremely large amount of inversion domain boundaries, the origin of which is attributed to stacking faults introduced during the initial stages of pressurization of hBN. 10) The change in color reflects this change in fine structure. The inversion domain boundaries could be an inhibition factor (energy barrier) in a reversible transition from wBN to original hBN, and is characteristic of a binary system.…”
Section: Structural Phase Transition Of Bn Polymorphsmentioning
confidence: 99%